O corpo, a doença e a saúde: o saber médico luso-brasileiro no século XVIII - Jean Luiz Neves Abreu (2006)
The Subject of this thesis is the study about conceptions over body, disease and health in the Luso-Brazilian context of XVIII century. Starting from the analyses of medicine treaties and other sources related, this research tries to approach the theories that have influenced the Luso-Brazilian medicine as well as the changes in the medical knowledge related to the Portuguese Enlightenment. The analysis of it allows to identify the presence of different perceptions about body related to hippocratian and galenian systems, magic and Mechanicism. Besides, this works analyses the influence medical theories related to health care. The Luso-Brazilian physicians and surgeons saugh to show prescriptions about hygiene and heath conservation, aiming to diminish the diseases spread and the death cases. The examination of that question allowed establishing links between medical knowledge and colonialism whereas the setters and the slaves body heath conservation became important to the Portuguese Crowd. The medical treaties were also dedicated to normative some questions related to diet, sexual practices, family and body exercises. Approaching this aspect, this work aims to indicate to effort of medical knowledge to draw its boundaries especially in relation to religion.